2008
DOI: 10.1099/mic.0.2008/020636-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mycoplasma genitalium MG218 and MG317 cytoskeletal proteins in terminal organelle organization, gliding motility and cytadherence

Abstract: The terminal organelle is a differentiated structure that plays a key role in mycoplasma cytadherence and locomotion. For this reason, the analysis of Mycoplasma genitalium mutants displaying anomalous terminal organelles could improve our knowledge regarding the structural elements required for proper locomotion. In this study, we isolated several M. genitalium mutants having transposon insertions within the mg218 or mg317 genes, which encode the orthologues of Mycoplasma pneumoniae HMW2 and HMW3 cytoskeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 38 publications
5
65
0
1
Order By: Relevance
“…The terminal structure of M. genitalium is composed of at least seven proteins, of which two (MgPa [also known as MG191], of 140 kDa [88] and P110 [also known as MG192]) are needed for adherence in collaboration with accessory proteins, such as the MG218 and MG317 proteins (156,169). By use of a ferritin-labeled monoclonal antibody to the M. genitalium 140-kDa adhesin protein, it has been shown that it clusters on the terminal portion of the organism (88).…”
Section: Biological and Physical Featuresmentioning
confidence: 99%
“…The terminal structure of M. genitalium is composed of at least seven proteins, of which two (MgPa [also known as MG191], of 140 kDa [88] and P110 [also known as MG192]) are needed for adherence in collaboration with accessory proteins, such as the MG218 and MG317 proteins (156,169). By use of a ferritin-labeled monoclonal antibody to the M. genitalium 140-kDa adhesin protein, it has been shown that it clusters on the terminal portion of the organism (88).…”
Section: Biological and Physical Featuresmentioning
confidence: 99%
“…The distinct flask-shaped morphology of M. genitalium cells can be attributed to its complex tip organelle involved in gliding motility (22)(23)(24)(25) and adherence to host cells and inanimate surfaces (26)(27)(28)(29)(30). Included among the tip organelle-associated proteins are the major adhesin, MgpB (also known as MgPa or P140), and its accessory protein, MgpC (also known as P110), which is required for the stability of MgpB (29).…”
mentioning
confidence: 99%
“…These two surface-exposed proteins are reciprocally stabilized (14) and clustered at the terminal organelle (15), a singular structure that polarizes the cell and assists in important functions such as cell adhesion, cell motility, and cell division (14,(16)(17)(18)(19)(20). MgpB and MgpC are also required for proper terminal organelle development (14) and regulate terminal organelle duplication during cell division by an unknown mechanism (21).…”
mentioning
confidence: 99%